Early victimization, drug use, and criminality - McClellan, Dorothy S. (Criminal justice and behavior, 1997)
Comparative analysis of the relative victimization of 1,030 adult male prisoners and 500 adult female prisoners in Texas reveals significant gender differences in childhood and adult maltreatment and subsequent substance use and criminality. Female inmates report significantly more maltreatment as children than do male inmates. Moreover, the maltreatment of women increases when they become adults, whereas the maltreatment of men drops sharply. The study found childhood maltreatment to be more strongly associated with adult depression and substance dependence among women than among men. The severity of substance misuse and problems associated with it are stronger predictors of female rates of criminal activity than male rates. Recent literature from the social sciences is presented to account for the findings. A female empowerment treatment model to help women attain control over their lives is suggested